Work-life balance as predictors of job satisfaction in the tertiary educational sector - Afia Nyarko Boakye; Richard Kofi Asravor; John Essuman (Cogent Business & Management, 2023)
This paper examines work-life balance as a predictor of job satisfaction in the tertiary education sector. The structural equation model was used to quantitatively analyse cross-sectional data gathered from 476 employees of 8 tertiary institutions operating in the Greater Accra region of Ghana. The study concludes that workplace support has a positive effect on personal life interference with work, and work interference with personal life. Work interference with personal life and personal life interference with work had a negative relationship with satisfaction with work life. The study recommends that personal life interference with work and work interference with the personal life of workers should be a priority of tertiary institutions, as it will help improve workplace support.
Keywords: 650; improved effectiveness at work; personal life interference; structural equation model; work interference with personal life; workplace supports